(untitled) (Al-Academy, 2018)
Over the last few years, the interior designer has been given the ability to access many innovative tools for new forms of unprecedented diversity and efficiency. Some design experts have described the new parametric procedures they are introducing to create new interior projects as a radical transformation that carries all the elements of a qualitative shift in interior design. The best of these parametric procedures is the technical capabilities offered by us to create new forms that are different from what has been discussed in everything that has been produced by designers and architects since modernity and even before it to the present time, which returns our design products through a series of computer programs that perform the processes that Simulates selective ecology of nature. However, it is wrong to believe that these parametric programs can be unconditionally loaded with a manager who controls their inputs and outputs. The designer is allowed to release them properly, let alone optimize them, and solve complex design issues without interference from the interior designer. Critical stages of the design process. Failures to intervene, adapt, or simply understand the algorithms given characteristics of the innovative form. Is entirely responsible for an unfortunate series of interior optimization and computerized systems analysis produced by the field of design so far. One thing that is clear to us is the definite convergence that takes place between interior design and other engineering disciplines, facilitated on the basis of data exchange through parametric modeling programs. The purpose of this research is to find creative approaches that celebrate the symbiotic and inevitable relationship in our present day between the interior designer and the computer. Founded by research and experimentation of a new dynamic method called parametricism characterized by its aesthetic effects in the interior design in the third millennium than previous movements and techniques producing the new form is certainly unprecedented.